2001
DOI: 10.1046/j.0953-816x.2001.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of extracellular hypocretin‐1 (orexin A) levels in the rat in relation to the light–dark cycle and sleep–wake activities

Abstract: Hypocretins/orexins are neuropeptides implicated in sleep regulation and the sleep disorder narcolepsy. In order to examine how hypocretin activity fluctuates across 24 h with respect to the sleep-wake cycle, we measured changes in extracellular hypocretin-1 levels in the lateral hypothalamus and medial thalamus of freely moving rats with simultaneous sleep recordings. Hypocretin levels exhibited a robust diurnal fluctuation; levels slowly increased during the dark period (active phase), and decreased during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
212
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(232 citation statements)
references
References 39 publications
17
212
0
3
Order By: Relevance
“…The arousal mediated by hypocretin neurons may be modulated by the energy state (Yamanaka et al, 2003b). That the two systems may subserve somewhat different functions is supported by analyses of daily rhythms; NE levels are reported to increase at the beginning of the wake period, whereas hypocretin levels increase later in the wake period (Mitome et al, 1994;Mochizuki and Scammell, 2003;Zeitzer et al, 2003), consistent with the view that hypocretin may generally oppose sleepiness during periods of prolonged wakefulness (Yoshida et al, 2001), whereas NE increases rapidly after waking.…”
Section: Functional Importance Of Ne Inhibition Of the Hypocretin Arosupporting
confidence: 64%
“…The arousal mediated by hypocretin neurons may be modulated by the energy state (Yamanaka et al, 2003b). That the two systems may subserve somewhat different functions is supported by analyses of daily rhythms; NE levels are reported to increase at the beginning of the wake period, whereas hypocretin levels increase later in the wake period (Mitome et al, 1994;Mochizuki and Scammell, 2003;Zeitzer et al, 2003), consistent with the view that hypocretin may generally oppose sleepiness during periods of prolonged wakefulness (Yoshida et al, 2001), whereas NE increases rapidly after waking.…”
Section: Functional Importance Of Ne Inhibition Of the Hypocretin Arosupporting
confidence: 64%
“…Receptors for orexin-A are located on neurons in many different brain regions making it possible for this peptide, once released, to activate a large number of areas affected by sleep and sleep deprivation (Hagan et al, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Piper et al, 2000;Gerashchenko et al, 2001;Yoshida et al, 2001;Wu et al, 2002;Peever et al, 2003;Lee et al, 2005;Mileykovskiy et al, 2005;Vittoz and Berridge 2006), It has recently been shown that manipulation of this system via administration of a orexin antagonist can increase sleep in rats, dogs and humans (Brisbare-Roch et al, 2007). The loss of orexin cells has been shown to cause human and animal narcolepsy (Chemelli et al, 1999;Lin et al, 1999;Nishino et al, 2000;Peyron et al, 2000;Thannickal et al, 2000;Gerashchenko et al, 2001;Wu et al, 2002;Mieda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in the extracellular orexin A levels in the lateral hypothalamic area are related to the light/dark cycle and sleep/wakefulness activities, and their release is increased after 6 h of sleep deprivation [28]. Given that orexin has an important role in the regulation of physiological sleep/wakefulness, our results suggest that the impairment of orexin neuronal activities may contribute to an increased amount of NREM sleep in HFD-induced obese mice.…”
Section: Discussionmentioning
confidence: 61%